Entre Imperial Eyes e “información fidedigna”. Reflexiones sobre la representación de América Central en textos de viajeros alemanes - Mackenbach, Werner (2016)
The texts written by European and North American travelers -travelogues, letters, reports, etc.- have played a major role in the production of Central American otherness and have had its repercussions in Central American literatures. Nowadays, there is an on-going debate about the value and epistemological status of these texts for the development of historical knowledge about Central American societies. The essay analyses three texts by German travelers in two historical key moments -mid nineteenth century and the nineteen-eighties of twentieth century- in the light of this theoretical and methodological debate and asks for the relevance of European travelogues for the representations of Central American realities and otherness in Central American literatures themselves from a transhistorical, epistemic, and “representational” rather than historical/ historiographical approach.